Analysis of Student Learning Motivation in Plant Anatomy Subject Prodi Tadris Biologi - Misahradarsi Dongoran; Ghina Yanti Harahap; Tri Putri Andriani Pane (Institut Agama Islam Negeri, 2023)
Plant anatomy is a branch of Botany that studies more complex structures in plants and the functions of each structure. Plant anatomy is one of the courses that must be taken or attended by students of Biology at the State Islamic University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan in semester 4. The course in Plant anatomy studies the internal structure of plants, both regarding cells found in plants, plant tissues and also about organs in plants. This study aims to determine student learning motivation in the Plant Anatomy Course, Tadris Biology Study Program, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan in the Plant Anatomy Course. The population and sample in this Plant Anatomy study were 4th Semester Students of the Tadris Biology Study Program, using a sampling technique, namely data collection techniques through observation, interviews and documentation. The results of data analysis through observation amounted to 56.10%, interviews amounted to 57.25%, documentation amounted to 48.22%. From the existing data, it can be determined that the factors of motivation to learn to see student learning interest with the highest percentage, curiosity, responsibility and attitude.